MULTIORGAN INVOLVEMENT IN AN ACQUIRED CYTOMEGALOVIRUS INFECTION IN AN INFANT: CASE REPORT - James Giraldo, Ingara (2022)
Acquired cytomegalovirus infection in most cases generates mild and self-limited symptoms. However, on some occasions it can present severe manifestations, findings that occur more frequently in premature or immunosuppressed patients. The objective of this research is to describe multiorgan involvement of an acquired cytomegalovirus infection with gastrointestinal, hepatic, neurological, cardiac and hematological involvement in a young infant. In order to achieve that, it’s presented the clinical case of a 3-month-old male patient, who is born at term, is admitted to the institution due to the presence of fever and diarrhea. Upon admission it is suspected sepsis of bacterial origin that rapidly evolves to multiorgan failure with hepatic and hematological involvement, which required ventilatory and vasopressor support. Cytomegalovirus infection is identified in cerebrospinal fluid, which required of the initiation of antiviral treatment with intravenous Ganciclovir. During hospitalization, the patient persists with diarrheal episodes, with elevated liver enzymes, with development of disseminated intravascular coagulation, with severe thrombocytopenia. Patient with persistent clinical deterioration developing dilated cardiomyopathy with severe systolic dysfunction and dying 11 days after hospital admission. The main conclusion of this research is that cytomegalovirus has the ability to generate severe and multisystemic manifestations even in acquired infections, for which it is necessary to know these unusual presentations to suspect this infection early and to be able to give a targeted treatment.   Key words: Cytomegalovirus, Multiple organ failure, Infant, Sepsis. Source: DeCS, BIREME.